2016
DOI: 10.1007/s10753-016-0413-4
|View full text |Cite
|
Sign up to set email alerts
|

Diosmin Modulates the NF-kB Signal Transduction Pathways and Downregulation of Various Oxidative Stress Markers in Alloxan-Induced Diabetic Nephropathy

Abstract: Hyperglycaemia-mediated oxidative stress plays an imperative role in the progression of diabetic nephropathy. NF-kB is an important transcription factor in eukaryotes which regulates a diverse array of cellular process, including inflammation, immunological response, apoptosis, growth and development. Increased expression of NF-kB plays a vital role in the pathogenesis of many inflammatory diseases including diabetic nephropathy. Hence, the present study was designed to explore the nephroprotective nature of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 82 publications
6
42
0
4
Order By: Relevance
“…16 In agreement with GST, animal experiments on LPO have yielded the same results. 17,18 In addition, genetic investigation also found that knockout of GST coding genes can lead to decreased GST levels and increased malondialdehyde (MDA) levels, an important biomarker of LPO, demonstrating that GST has an effect against oxidative stress. 19 Human research was consistent with the experimental studies above.…”
Section: Biomarkers Of Glutathione Antioxidant System and Lipid Peroxmentioning
confidence: 99%
“…16 In agreement with GST, animal experiments on LPO have yielded the same results. 17,18 In addition, genetic investigation also found that knockout of GST coding genes can lead to decreased GST levels and increased malondialdehyde (MDA) levels, an important biomarker of LPO, demonstrating that GST has an effect against oxidative stress. 19 Human research was consistent with the experimental studies above.…”
Section: Biomarkers Of Glutathione Antioxidant System and Lipid Peroxmentioning
confidence: 99%
“…A caracterização dos estudos e os resultados acerca da Diosmina foram relatados e expostos na Figura 1. [16][17][18][19][20][21][22][23] , contribuindo para a redução das lesões cardíacas, hepáticas e renais induzidas em muitos modelos de experimentação animal (Tabela 1).…”
Section: Métodounclassified
“…For type 2 diabetes rats, similarly, upregulation of malondialdehyde and downregulation of antioxidant enzymes, such as superoxide dismutase and glutathione, were observed in diabetes rat kidney. And, restoration of these enzymes halted hyperglycemia-induced oxidative stress and maintained renal function [14]. Moreover, it is not difficult to obtain similar evidence from clinical studies [1517].…”
Section: Oxidative Stress and Dnmentioning
confidence: 99%